PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF MATA PELAJARAN IPA FISIKA PESERTA DIDIK KELAS IX SMPN 1 BANTAN - Kartini '; Zuhdi Ma’ruf; M. Rahmad ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: This research aimed to describe and find out the improvement of the result of physics learning student class IX of SMPN 1 Bantan and to explain the significant contradiction the result of physics learning between student that have been learn by the conventional method with the student that have been learn by the cooperatif learning model type Course Review Horay. The type of research is a quasi-experimental, with Intact Group Comparisson design. The subject of this research is students class IX at SMPN 1 Bantan, total of 40 students as divide into two class, experimental class and control class. The data in this research is a score of the result before and after learning physics by implementation of cooperative learning model type Course Review Horay and analysis of the data uses descriptive analysis and inferential analysis. Then, measured the increase the result by normalized gain (gain-N). The result of this research, from descriptive analysis got score result of students at experimental class in high category with N-Gain 0,71, and the control class in the middle category with N-Gain 0,46. From inferential anylisis show that there has significant contradiction the result of physics learning between student that have been learn by the conventional method with the student that have been learn by the cooperatif learning model type Course Review Horay. Therefore, it can be concluded that the implementation of cooperative learning model type Course Review Horay can to increase the result of physics learning student class IX SMPN 1 Bantan and be found the significant contradiction the result of physics learning between student that have been learn by the conventional method with the student that have been learn by the cooperatif learning model type Course Review Horay.